Co-Designing Ethical AI with Faith Communities: Advancing Worship Innovation, Moral Governance, and Resilient Digital Ecosystems - Olayinka, Oyunwola Taiwo; Temitope, Oyebanji Israel; Thomas, Adebimpe Seun; Oluwole, Ademola Peter (Darul Yasin Al Sys, 2025)
This research explores the collaborative development of ethical artificial intelligence (AI) tools with religious communities to enhance worship practices, inform moral decision-making, and support social cohesion. As AI technologies increasingly intersect with spiritual life—through applications such as automated liturgy generators and pastoral chatbots—there is an urgent need to ensure these systems uphold religious values and contribute positively to community well-being. While existing AI ethics frameworks are largely rooted in secular paradigms, few integrate religious epistemologies or position faith groups as active partners in design processes. Addressing this gap, the study investigates how religious communities and AI specialists can co-create systems that align with sacred values and promote communal resilience. Employing a participatory action methodology, the research engaged multi-faith dialogue groups, collaborative design sessions involving theologians and programmers, and case studies from Christian, Muslim, and Traditionalist communities in Nigeria. Findings indicate that effective integration of AI in religious contexts is contingent upon context-sensitive moral reflection, transparent data governance, and trust in institutions. The study argues that ethical AI for religious use must emerge from genuine collaboration rather than external imposition. It recommends the establishment of interfaith technology centers, the direct involvement of theologians in AI development teams, and the formulation of governance models informed by religious ethics and local priorities. These measures not only safeguard religious practices but also contribute to equitable and sustainable digital ecosystems aligned with global development objectives.